Meroterpenoids From Ganoderma lucidum Mushrooms and Their Biological Roles in Insulin Resistance and Triple-Negative Breast Cancer - Zhang, Jiao-Jiao; Wang, Dai-Wei; Cai, Dan; Lu, Qing; Cheng, Yong-Xian (Frontiers in Chemistry, 2021)
Ganoderma fungi as popular raw materials of numerous functional foods have been extensively investigated. In this study, five pairs of meroterpenoid enantiomers beyond well-known triterpenoids and polysacchrides, dayaolingzhiols I−M (1−5), were characterized from Ganoderma lucidum. Their structures were identified by spectroscopic and computational methods. Structurally, compound 1 features a novel dioxabicyclo[2.2.2]octan-3-one motif in the side chain. Ethnoknowledge drived biological evaluation found that (+)-5 could activate Akt and AMPK phosphorylation in insulin stimulated C2C12 cells, and (+)-5 could activate glucose uptake dose dependently in C2C12 cells. Further, we found that (+)-1, (+)-4, and (–)-4 could significantly inhibit cell migration of MDA-MB-231 cell line, of which (+)-4 showed significant inhibitory effect against cell migration of MDA-MB-231 cell line in a dose dependent manner. These findings revealed the meroterpenoidal composition of G. lucidum and their roles in the prevention of chronic diseases such as diabetes mellitus and triple negative breast cancer.